The problems of the framework of practical identity of a person in analytic philosophy - Olifer Олена (Actual Problems of Mind, 2024)
The article concerns the problem of personal identity in analytic philosophy as the maintenance of a person’s self-identity over time. It describes a framework of practical identity, which is based on the thesis that personal identity consists in rational unity, i.e. the integrity of the Self achieved through doing actions. This way to describe identity emphasizes its processual nature. According to it, personal identity is maintained through the constant attribution of actions, when a person ascribes his or her actions to himself or herself and regards them as own. Philosophers, who justify the framework of practical identity as an alternative to the metaphysical one, argue that the practical framework not only explains how identity is formed and maintained over time, but also comprises issues concerning a person’s practical activities. Therefore, it is considered to have broader applicability than the metaphysical one. In this article, we offer to test both the ontological and practical models of personal identity in the thought experiments about time travel and amnesia, which are considered in both philosophy and popular culture. We demonstrate that the framework of practical identity is not applicable in all cases to explain the practical problems of a person’s existence. Thus, the purpose of our paper is to determine why such issues arise when describing personal identity in the practical framework. The article argues that reidentification, the way to maintain identity over time, leads to the disappearance of qualitative distinctions between different person stages, and as a result, the personal narrative becomes too subjective and unrelated to a person’s real life. Moreover, it does not encompass the individual’s entire life, which is also a problem for the practical framework of personal identity. To find a possible solution to these problems in the framework of practical identity, we suggest reconsidering it from the perspective of social philosophy. We claim that activity necessarily involves the participation of others, and therefore, social interaction should be considered as the basis of personal identity.